Problems in the diary sector from a political point of view: Actors and sectorial forms of representation in the last period - Nogueira, María Elena (Centro de Historia Argentina y Americana, 2010)
This paper analyzes, from a political perspective, the associative universe existing within the argentine diary sector by establishing the institutional forms, speeches and practices that it presents. The analysis is justified by the relevance that the social actors have in the policy concertation processes carried by the National State since the recuperation of democracy. A reflection of this universe is a relevant explicative tool at the moment of analyzing the current policies. The methodology used for the realization of this project is qualitative, from researches of journalistic material, interviews and a bibliographic research of the subject.